Coastal fisheries of Argentina - Elias, Ines (2011)
Over centuries the coasts of Argentina were inhabited by aboriginal peoples that, mostly towards the south, harvested marine resources. The archaeological record shows evidence of consumption of mammals, amphibians, molluscs and fishes along Patagonian shores. The gathering methods and knowledge of these early fishers were not, however, incorporated by the colonial society, contrary to what was the case in Peru and Chile, which became leading countries with regard to artisanal fishing activities. It is perhaps because of this, together with prevalent policies that prioritized agriculture and husbandry, that fishing and fishers are perceived as exotic (Mateo Oviedo, 2003).